Be Careful What You Wish For: An Examination of Arrest and Prosecution Patterns of Domestic Violence Cases in Two Cities in Michigan - Lyon, Andrea D. (1999)
This Article will examine six months of data on arrests for domestic violence in the cities of Ypsilanti and Ann Arbor. In order to be able to interpret what the data means Lyon did some other research. The results were surprising- for example, although women tend to be injured most severely by domestic violence, they use violence in intimate relationships a little more often than men. Part I of this Article traces a brief history of domestic violence and discusses the issue of who commits domestic violence, Part II discusses the must arrest and should arrest policies and their history, Part III lays out what the data received from Ann Arbor and Ypsilanti revealed, and Part IV addresses the policy implications of this information and proposes some changes